Theological defense for human rights in Indonesia - Aristo Purboadji (Cogent Arts & Humanities)
This article argues that the surest and sincerest religious tolerance is one based upon the acceptance of the universality of human rights, and in the Indonesian context, such acceptance is best secured through Religious Education (RE). This paper further presents considerations for RE based on the political theology of human rights, augmented by the theology of human flourishing and greater emphasis on responsibility, within each recognized religion in Indonesia. Two exemplary cases of the political theology of human rights are highlighted within Christianity and Islam, (1) Miguel Vatter’s interpretation of Maritain’s political theology and (2) Mustafa Akyol’s (re)interpretation of Islamic theology. They are highlighted due to their unique interpretation of Scripture for the basis of the universality of human rights, namely Maritain’s Pauline notion of ‘sons of God’ and Akyol’s Addamiyah. Scholarly studies have depicted human rights culture (as a form of political culture) as an important determining factor in democratic consolidation, and in many cases, one notable obstacle to such human rights culture is religious/theological objections to human rights.